Medical jurisprudence from the judicial standpoint - Smith, W. Ramsay (The University of Edinburgh, 1913)
Medical jurisprudence, as Casper said, is a science of itself, and not a mere encyclopaedia of the other medical sciences. In the following chapters J. have set myself the novel task of viewing the principles and practice of medical jurisprudence from the stand-point of the court, the bench, the Judge. The broad principles of law as they come before the jurist in connection with all proceedings, whether medico- legal or not, are set forth. The law of England, including its recent trend, as applicable to the medico-legal subjects most commonly before the courts, is stated; the nature of the medical evidence required as legal proof in canes at issue is shown; and the present position of medical science in relation to facts required in evidence is sketched in greater or less detail as the circumstances seem to demand. From an accumulated mass of materials, legal and medical, culled from others and from original observations and experiment I have selected illustrative examples, showing the methods of science, in its various departments, applied to medico-legal investigation, especially in criminal cases.